Medieval Nonsense Signifying Nothing in Fourteenth-Century England - Kirk, Jordan; Project Muse. (New York : Fordham University Press, 2021)
"In a series of close and unorthodox readings of works by Priscian, Boethius, Augustine, Walter Burley, Geoffrey Chaucer, and the anonymous authors of the Cloud of Unknowing and St. Erkenwald, Jordan Kirk reveals the way that writers across the fourteenth century reckoned with the word as mere sound. Medieval Nonsense rebuts the idea that single-minded devotion to the kernel of meaning within the word motivated these authors in their engagement with vox sola, the mere utterance. Rather, they recognized the possibilities inherent in the accounts of language transmitted to them from antiquity, and they transformed those accounts into new ideas, forms, and practices of nonsignification"--
The Wind in the Shell: Prolegomena to the Study of Medieval Nonsignification -- Priscian, Boethius, and Augustine on Vox Sola -- Walter Burley on Suppositio Materialis -- The Cloud of Unknowing on the Litil Worde of O Silabe -- St. Erkenwald on the Caracter.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Philosophy, Medieval; Nonsense literature, English -- History and criticism; English literature -- Old English, ca. 450-1100 -- History and criticism; Philosophie médiévale.; Littérature nonsensique anglaise -- Histoire et critique; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; LITERARY CRITICISM / Semiotics & Theory; English literature -- Old English; Nonsense literature, English; Philosophy, Medieval; 450-1100; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.